Epsilon poly-L-lysine as a novel antifungal agent for sustainable wood protection - Cai, Lili; Kuo, Chi-Jui (Frontiers in Microbiology, 2022)
There has been a growing interest in seeking natural and biobased preservatives to prevent wood from deterioration during its service life, thus prolonging carbon storage in buildings. This study aims to assess the in vitro and in vivo antifungal properties of Epsilon Poly L-lysine (EPL), a secondary metabolite from actinomyces, against four common wood-inhabiting fungi, including two brown-rot Gloeophyllum trabeum (GT) and Rhodonia placenta (RP), and two white-rot fungi, Trametes versicolor (TV) and Irpex lacteus (IL). Our results indicate that these fungi responded differently upon EPL treatment. From in vitro study, the minimal inhibitory concentration of EPL against GT, TV and IL was determined to be 3 mg/ml, while that of RP was 5 mg/ml. EPL treatment also affects the morphology of the hyphae by changing from a smooth surface with a tubular structure to twisted and deformed shapes. Upon EPL treatment with wood samples (in vivo), it was found that EPL could possibly form hydrogen bonds with the hydroxy groups in wood and was uniformly distributed across the transverse section of the wood samples, as indicated by Fourier transform infrared spectroscopy and fluorescence microscopy analysis, respectively. Compared to control wood samples with a mass loss of over 15% across different fungi, wood samples treated with 1% EPL showed negligible or very low (<8%) mass loss. Additionally, the thermal stability of EPL-treated wood was also improved by 50%. This study suggests that EPL could be a promising alternative to traditional metallic-based wood preservatives.